A representação da informação do documento de arquivo: perspectivas metodológicas para elaboração de pontos de acesso - Cândido, Gilberto Gomes [UNESP] (2014)
The course of this study is based by the interdisciplinarity, once it seeks to identify methods that are in other areas and fields of knowledge, with a view to provide theoretical and practical discussions, from methodological notes about the Diplomatics Archives, Document Analysis and Generative Trajectory of Meaning. Having that in mind, the object of this study is the document file in its permanent stage in the physical state. At this stage, the document file is submitted to the description in which its content is described to provide access and information retrieval. This description is realized/achieved taking as basis international standards such as the General International Standard Archival Description (ISAD (G)) and the International Standard Archival Authority Record for Corporate Bodies, Persons and Families (ISAAR (CPF)), about the Brazilian Standard Archival Description (NOBRADE); these propose standardization of the description, from common elements, presented in their levels of description. These norms focus on the development of research instruments, presenting them in the Guide, Inventory and catalog format, enabling the access and the information retrieving in the permanent phase, however, these can be used in other documentary phases. The research instruments, like in the description, are applied in the permanent phase. However, it stresses that the norms do not commit to the input or output data, as well as research instruments are borne by each custodian institution for its elaboration. So, the problem of this research is the lack of develop methods that help the archivist to represent and provide access to information and the degree of the necessity to have them in this area. At this point, when we search in norms a way of represent the archive documents, we faced with the term access point, that in a general comprehension, are terms extracted from the document and compiled to proportion the access. However, as...